A modified embedded discrete-fracture model to study oil-water two-phase heat and mass transfer in the complex fracture network. (August 2021) - Shi, Junjie; Cheng, Linsong; Rao, Xiang; Cao, Renyi; Liu, Gaoling
Highlights: An EDFM method with high precision and high robustness is proposed to solve the coupled solution of temperature field and seepage field. Accurate calculate of mass transfer and heat transfer between matrix and fracture by boundary element method. The influence of temperature field change in the reservoir on the seepage field can not be ignored ABSTRACT: The temperature of the fluids injected is usually cooler than the in-situ reservoir temperature in the fractured reservoir's development. It is essential to study thermal changes between matrix and fracture. This paper establishes a fully implicit solution model for the coupling of the oil-water two-phase temperature field and seepage field based on the embedded discrete fracture model (EDFM) method. We deduced the mass and heat transfer between the local matrix grid and the fracture grid by the boundary element method (BEM) instead of a simple linear hypothesis to improve the traditional EDFM method. The model can accurately calculate the seepage field and temperature field in the two-dimensional or three-dimensional problem. Compared with the analytical solution, the discrete fracture model (DFM) and the traditional EDFM method proved that the modified EDFM method could significantly improve the calculation accuracy(especially the temperature field). Furthermore, the modified EDFM method is applied to four examples: waterflooding, huff and puff development, heterogeneous and natural fractured reservoirs, and multilayer enhanced geothermal system (EGS), which verifies the applicability, robustness, and computational convenience, of the new method and illustrates the influence and necessity of considering the coupling effect of temperature field and seepage field on the development effect. It provides an efficient and accurate new method for the study of non-isothermal seepage in fractured reservoirs.